Red cell distribution width (RDW) is correlated to time of oxygen desaturation < 90% and length of sleep apneas in patients with sleep disorder breathing (SDB) and acute heart failure with preserved ejection fraction (HFpEF) - Stamerra, Cosimo A.; D'Elia, Emilia; Gori, Mauro; Roncali, Federica; Cereda, Alberto; Gavazzi, Antonello; Ferri, Claudio; Senni, Michele (Frontiers in Cardiovascular Medicine, 2023)
Background: SDB (sleep disorder breathing) is a frequent comorbidity of heart failure with preserved ejection fraction (HFpEF). Red cell distribution width (RDW) has been previously documented to be a valuable surrogate marker of inflammation, and to be associated with hypoxia and oxidative stress. Aim: To evaluate a possible correlation between RDW, sleep apnea, and oxygen saturation (SaO2) in a population of acute HFpEF (AHFpEF) patients with SDB. Methods: We investigated a population AHFpEF patients with history of SDB. A set of laboratory markers, a complete echocardiogram, and a 24 hours polysomnography (PSG) were performed during hospitalization. Results: A total of 34 acute HFpEF patients (mean age 72.8 +/- 8.63) were enrolled in the study. A control group of 24 non-HF patients were considered. Compared to controls, HFpEF patients showed a higher mean apnea hypopnea index (AHI), with prevalence of central apneas. A moderate to severe desaturation pattern was observed in AHFpEF vs controls. RDW was significantly higher in AHFpEF patients vs controls (mean value 14.7 +/- 2.6 % vs 9.1 +/- 2.2, p < 0.05). In AHFpEF, RDW showed a positive correlation with time of SaO2 < 90% (r = 0.35, p =0.04), and with mean length of apneic events (60 +/- 28 seconds, r= 0.29, p=0.03). Conclusion: In patients with AHFpEF and SDB, a correlation between RDW and both time and length of oxygen desaturation was observed, as if oxidative stress and inflammatory processes linked to RDW increase could be involved in the desaturation pattern in these patients.